The Utilization of Reproductive Health Services for Adolescents in Tegallalang I Health Centre - Deni Witari; Ni Luh Putu Suariyani; I Nyoman Mangku Karmaya (Universitas Udayana, 2014)
Background and purpose: Adolescence is one of the most crucial periods of a human’s life cycle, and therefore, there is an unquestionable need for services that directly address adolescent reproductive health issues. The number of adolescents who utilized reproductive health services at Tegallalang I Health Centre is only 119 out of 708 targeted adolescents. This study investigate the correlation between knowledge, attitude, adolescent needs, access, family acceptability, and the utilization of reproductive health services in Tegallalang I Health Centre. Methods: The design was a cross sectional analytic. From the population of 4725 adolescents in the Tegallalang I Health Centre work area, 84 were selected through systematic random sampling. The independent variables were knowledge, attitude, adolescent needs, access and family acceptability while the dependent variable was the utilization of adolescent reproductive health service. Data was collected through structured interviews and analysed using univariate, bivariate (chi-squared test), and multivariate (logistic regression) analysis. Results: The results of this study showed that most respondents have high level of knowledge (54.8%), negative attitudes (69.0%)), perceived need (59.5%), ease of access (52.4%), negative family acceptability (60.7%)), and (62.0%) do not take advantage of services. Based on the bivariate analysis it is evident that there is a relationship between knowledge (p=0.043), attitude (p=0.047), access (p=0.08), family acceptability (p=0.042) and the utilization of reproduction health service. Based on multivariate analysis, it is evident that access has a positive influence on the utilization of reproductive health service with OR=3.481 (95%CI: 1,21-10,24). Conclusion: Access has a positive influence on the utilisation of reproductive health service in Tegalalang I Health Centre.